Reading Anxiety Experienced by Senior High School Students (A Case Study in the Senior High School 1 Ciawigebang) - Fauziah Ayuningsih; Vina Agustiana; Wulan Rahmatunisa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2021)
This paper aims to find out the level of reading anxieties experienced by senior high school students andto identify the major factors that influence anxieties experienced by the students. Mix method research design was applied in this research. There are 36 students employed in this research. The data were collected through questionnaire and interview. The data were analyzed within two phases, the first is quantitatively in order to find out the level of reading anxiety experienced by senior high school student and the second is qualitatively in order to identify the major factor triggering the reading anxiety. The results of the research reveals that level reading anxiety is in high level with score 68.08. The result also shows that students experienced high level of anxiety in all category, namely worry about effect (71.85), fear of making error (60.69), unfamiliar culture (70.42), unfamiliar topic (62.5), unknown vocabulary (70.28) which all category is in the high level. Thus, the major factor triggering reading anxiety experienced by senior high school students is worry about effect.